Angkutan Sedimen Sungai Siak disekitar Pilar Jembatan Siak I - Risenal Nick; Virgo Trisep Haris; Fitridawati Soehardi (JURNAL TEKNIK UNILAK, 2020)
Siak River is one of the primary rivers in Riau province, so that this river holds and flows water runoff from the left and right areas along the river flow. As a result of changes in sediment transport discharges resulted in degradation in the riverbed of Siak, resulting in the collapse of the bridge. Concerns due to the collapse of several bridges over the Siak River and seeing the condition of the Siak Bridge I need to calculate how much the sediment river sediment transport is around the Siak bridge pillar. The method used to analyze the data uses the Yang's method and hydraulic concept, based on the results of the analysis and calculation of sedimentation transport due to maximum discharge, the largest sediment transport is 3,753,25924 kg / day.